2018
DOI: 10.1371/journal.ppat.1007048
|View full text |Cite
|
Sign up to set email alerts
|

A lipid-binding loop of botulinum neurotoxin serotypes B, DC and G is an essential feature to confer their exquisite potency

Abstract: The exceptional toxicity of botulinum neurotoxins (BoNTs) is mediated by high avidity binding to complex polysialogangliosides and intraluminal segments of synaptic vesicle proteins embedded in the presynaptic membrane. One peculiarity is an exposed hydrophobic loop in the toxin’s cell binding domain HC, which is located between the ganglioside- and protein receptor-binding sites, and that is particularly pronounced in the serotypes BoNT/B, DC, and G sharing synaptotagmin as protein receptor. Here, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 75 publications
5
35
0
Order By: Relevance
“…Functionally, H C determines neuronal specificity by recognizing a polysialoganglioside (e.g., GT1b) and a protein receptor, synaptotagmin (Syt) I/II (for BoNT/B, /G, and /DC) or glycosylated synaptic vesicle protein 2 (SV2) (for BoNT/A, /D, /E, and /F), located on the presynaptic membrane (Chai et al, 2006;Jin et al, 2006;Montecucco, 1986;Stenmark et al, 2008;Yao et al, 2016). H C of BoNT/B, /G, and /DC additionally carries a hydrophobic loop, termed the H Cloop, which interacts with host membrane lipids (Stern et al, 2018;Zhang et al, 2017;Figure 1A). Under acidic conditions, the H N undergoes a pH-induced structural rearrangement and forms a protein channel that delivers the unfolded LC to the cytosol (Fischer et al, 2012;Koriazova and Montal, 2003;Lam et al, 2018;Montal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, H C determines neuronal specificity by recognizing a polysialoganglioside (e.g., GT1b) and a protein receptor, synaptotagmin (Syt) I/II (for BoNT/B, /G, and /DC) or glycosylated synaptic vesicle protein 2 (SV2) (for BoNT/A, /D, /E, and /F), located on the presynaptic membrane (Chai et al, 2006;Jin et al, 2006;Montecucco, 1986;Stenmark et al, 2008;Yao et al, 2016). H C of BoNT/B, /G, and /DC additionally carries a hydrophobic loop, termed the H Cloop, which interacts with host membrane lipids (Stern et al, 2018;Zhang et al, 2017;Figure 1A). Under acidic conditions, the H N undergoes a pH-induced structural rearrangement and forms a protein channel that delivers the unfolded LC to the cytosol (Fischer et al, 2012;Koriazova and Montal, 2003;Lam et al, 2018;Montal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The role of LBLs in BoNT/B, C, D, G, and DC for binding to lipid membranes has been hypothesized previously. Mutagenesis studies have demonstrated the importance of LBL for forming stable binding to membrane-embedded receptors and for the potency of these toxins [64][65][66][67][68]71]. However, it has been challenging to detect direct binding of these toxins to lipid membranes because protein−lipid interactions are usually transient and of rather low binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the effect of lipid binding in the presence of Syt II, we compared binding of H C /B versus H C /B WW for ND-Syt. As binding of H C /B to Syt II has a relatively high affinity, with K D approximately 10 −7 M [46,47,71], we resorted to the more-sensitive Octet RED 384 system for BLI assays and titrated the H C concentrations from 2 μM down to 5 nM (Fig 4D-4F). Binding responses, total binding levels, and dissociation rates were all similar between WT H C /B and H C /B WW .…”
Section: Plos Biologymentioning
confidence: 99%
See 2 more Smart Citations